Inventory of microalgae at Sepanjang Beach the coastal area of Gunung Kidul Jogjakarta - Roziaty, Efri; Akbar, Shohifa Aulia (Universitas Muhammadiyah Surakarta, 2018)
Research conducted in the coastal area along Sepanjang Beach Gunung Kidul Jogjakarta aims to find out what types of microalgae are present in the region. The area of Sepanjang Beach Gunung Kidul Jogjakarta is one of the most favourite beach visited by tourists both domestic and foreign. The research was conducted in March - October 2018. The sampling method used was Purpossive Sampling where it was determined as many as 5 sampling points called the Station. Then at each station created 2 substations are made as replications. From the results of the study found as many as 12 species from 4 families namely Bacillariophyceae, Chlorophyceae, Euglenophyceae and Cyanophyceae. Of the four families produced 12 species including Navicula sp., Euglena viridis, Spirulina sp. and Oscillatoria sp. It indicates that the environment is still good.